(untitled) (Medico Legal Update, 2019)
The purpose of this study is to identify the moderating effects of disability acceptance in the effects of discrimination experience of the disabled on the quality of life. In this case, the analysis method included using SPSS 21.0, frequency analysis, crossover analysis, and reliability analysis were performed. Additionally, the T-test, and ONEWAY ANOVA were applied. The adjustment effect of the noted disability acceptance was identified using the SPSS MACRO PROCESS 1. First, the level of adjustment of disability acceptance in the influence of discrimination experience of disabled on the sense of happiness, in the case of medium and high values, it was shown that 94% was significant. Second, it was found that discrimination experience, disability acceptance, and discrimination experience x disability acceptance all had a significant effect on the sense of happiness. In the effect of the discrimination experience of the disabled on the sense of happiness, the moderating effect of disability acceptance has been verified. In other words, even if there is a problem of happiness due to the discrimination experience of the disabled, when the degree of disability acceptance was high, it was found that sense of happiness was improved even more. As a suggestion for future research, first, although in this study, the moderating effects of disability acceptance in the relationship between discrimination experience and happiness was examined, the difference according to the age or gender of disabled people were not verified. Therefore, by using the age and gender of the disabled as control variables or parameters in future studies, the effect of acceptance of disability can be seen more clearly. Second, as limitations of the data, this study has analysed focusing only on the sense of happiness, but there is a need to expand the positive effect of disability acceptance by using variables such as stress, life satisfaction, suicidal thoughts, and self-esteem as dependent variables.